2021
DOI: 10.3389/fcell.2021.802745
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Roles and Clinical Implications of Non-Coding RNAs in Gastric Cancer

Abstract: Gastric cancer (GC) is one of the most common malignancies in the world. It is also the fifth most common cancer in China. In recent years, a large number of studies have proved that non-coding RNAs (ncRNAs) can regulate cell proliferation, invasion, metastasis, apoptosis, and angiogenesis. NcRNAs also influence the therapeutic resistance of gastric cancer. NcRNAs mainly consist of miRNAs, lncRNAs and circRNAs. In this paper, we summarized ncRNAs as biomarkers and therapeutic targets for gastric cancer, and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 245 publications
0
4
0
Order By: Relevance
“…In gastric carcinoma, miRNAs also regulate cell proliferation and migration by targeting PTEN and EGFR, as well as MAPK pathways, and EZH2, which participates in chromatin remodeling [ 126 , 127 , 129 ]. Numerous miRNAs in this disease are related to resistance to apoptosis through the regulation of Bcl2 or other members of its family, angiogenesis, and resistance to chemotherapy [ 132 , 133 , 134 , 217 ].…”
Section: Mirna In Malignant Tumorsmentioning
confidence: 99%
“…In gastric carcinoma, miRNAs also regulate cell proliferation and migration by targeting PTEN and EGFR, as well as MAPK pathways, and EZH2, which participates in chromatin remodeling [ 126 , 127 , 129 ]. Numerous miRNAs in this disease are related to resistance to apoptosis through the regulation of Bcl2 or other members of its family, angiogenesis, and resistance to chemotherapy [ 132 , 133 , 134 , 217 ].…”
Section: Mirna In Malignant Tumorsmentioning
confidence: 99%
“…Non-coding ribonucleic acids (RNAs) mainly consist of short/small RNAs, circular RNAs, and those greater than 200 bases, who are called long non-coding RNAs (lncRNAs) [ 6 , 7 ] . Although the biological function of IncRNAs have not been thoroughly investigated, numerous IncRNAs have been proved as powerful regulators of diverse human diseases [ 8 , 9 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Lately, accumulative evidence revealed that non-coding RNAs (ncRNAs) played pivotal roles in regulating gene expression [4,5] and can affect the cancer process by regulating alternative splicing [6,7]. NcRNAs, which are a group of RNAs that do not have protein coding function, contain many categories.…”
Section: Introductionmentioning
confidence: 99%